Clinical Utility of the Trail‐Making Tests as a Predictor of Driving Performance in Older Adults. Issue 11 (27th October 2015) - Papandonatos, George D.; Ott, Brian R.; Davis, Jennifer D.; Barco, Peggy P.; Carr, David B.
Abstract : Objectives: To assess the clinical utility of the Trail‐Making Tests (TMTs) as screens for impaired road‐test performance. Design: Secondary analyses of three data sets from previously published studies of impaired driving in older adults using comparable road test designs and outcome measures. Setting: Two academic driving specialty clinics. Participants: Older drivers (N = 392; 303 with cognitive impairment, 89 controls) from Rhode Island and Missouri. Measurements: Standard operating characteristics were evaluated for the TMT Part A (TMT‐A) and Part B (TMT‐B), as well as optimal upper and lower test cut‐points that could be useful in defining groups of drivers with indeterminate likelihood of impaired driving who would most benefit from further screening or on‐road testing. Results: Discrimination remained high (>70%) when cut‐points for the TMTs derived from Rhode Island data were applied to Missouri data, but calibration was poor (all P < .01). TMT‐A provided the best utility for determining a range of scores (68–90 seconds) for which additional road testing would be indicated in general practice settings. A high frequency of cognitively impaired participants unable to perform the TMT‐B test within the allotted time limited the utility of the test (>25%). Mere inability to complete the test in a reasonable time frame (e.g., TMT‐A > 48 seconds or TMT‐B > 108 seconds) may still be a useful tool in separating unsafe from safe or marginal drivers in such samples. Conclusion: The TMTs (particularly TMT‐A) may be useful as screens for driving impairment in older drivers in general practice settings, where most people are still safe drivers, but more‐precise screening measures need to be analyzed critically in a variety of clinical settings for testing cognitively impaired older drivers.